Sige Tareik Nafah - Faisal Faisal (Hukum Keluarga Islam IAIN LANGSA, 2021)
There is a phenomenon that occurs in Langsa City regarding the understanding of some Imum Gampong (Village Imams) and some community leaders who argue that in the pronunciation of the ijab-qabul lafadz spoken by the bride's guardian or by the prospective groom, it must be sige tareik nafah. This sige tareik nafah, as said by Tengku imum gampong (village priest), is very burdensome for the prospective groom or guardian, because in addition to the long sentences, nervousness becomes an obstacle and interferes with concentration in pronouncing consent, so many feel afraid before the implementation of the marriage contract, such rules or customs seem too excessive. This article uses the sociology of law theory. The results of the study show that the scholars of Langsa City in this matter are a habit or custom that develops in society, so that the gampong priests understand it as a legal stipulation, then in pronouncing the ijab-qabul it must be with sige tareik nafah, otherwise the marriage is invalid. . Then this sige tareik nafah is an addition to the understanding of the village priest about the prohibition of fashl in pronouncing the ijab-qabul and the qabul-qabul must be in one assembly.